Educational contributions to students’ belongingness to the society, neighbourhood, school and family - Chau-kiu Cheung; Hoi Yan Cheung; Ming-tak Hue (International Journal of Adolescence and Youth, 2017)
A way that education is desirable is its integrative function for society and its sectors, according to structural-functionalist theory. This function consists in the promotion of the student’s belongingness to society and its sectors. In consolidating empirical support for the function, this present study analyses survey data on 417 students in Hong Kong, China. Results show that the student’s academic achievement had significant positive effects on belongingness to the society, neighbourhood and school. In addition, the student’s educational level displayed a significant positive effect on belongingness to society. In endorsing the integrative function of education, the results imply the merit of promoting education to enhance the student’s belongingness.